Review of the Mimela species of the Dalat Plateau in southern Vietnam (Coleoptera, Scarabaeidae, Rutelinae). - Prokofiev, Artem M.; Zorn, Carsten (Contributions to Entomology = Beiträge zur Entomologie, 2016)
Twelve species of Mimela are recorded from the Dalat Plateau in southern Vietnam of which ten are described as new to science. The majority of species appear to be endemics and have Sino-Himalayan relatives. Keywords Coleoptera, Scarabaeoidea, Scarabaeidae, Rutelinae, Anomalini, Mimela, Vietnam, Dalat, new species, taxonomy, Oriental region. Nomenclatural Acts amphichroma Zorn & Prokofiev, 2016 (Mimela), spec. nov. campyloclados Zorn & Prokofiev, 2016 (Mimela), spec. nov. dalatocoerulea Zorn & Prokofiev, 2016 (Mimela), spec. nov. galbinata Zorn & Prokofiev, 2016 (Mimela), spec. nov. germana Zorn & Prokofiev, 2016 (Mimela), spec. nov. indosinica Zorn & Prokofiev, 2016 (Mimela), spec. nov. krasava Zorn & Prokofiev, 2016 (Mimela), spec. nov. langbianica Zorn & Prokofiev, 2016 (Mimela), spec. nov. pacholatkoi Zorn & Prokofiev, 2016 (Mimela), spec. nov. vietnamensis Zorn & Prokofiev, 2016 (Mimela), spec. nov.